2021
DOI: 10.5614/itbj.ict.res.appl.2021.15.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Serious Game Development Model Based on the Game-Based Learning Foundation

Abstract: Serious games or applied games are digital games applied in serious fields such as education, advertising, health, business, and the military. Currently, serious game development is mostly based on the Game Development Life Cycle (GDLC) approach. A serious game is a game product with unique characteristics that require a particular approach to its development. This paper proposes a serious game development model adapted from the Game-Based Learning Foundation. This paper’s main contribution is to enhance knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…GDLC was chosen in this study because it has been widely used by previous researchers and has proven to be an appropriate game development method if implemented in game design. This method has simple steps and is by the conditions in this study as shown in Figure 1 [18][19] [20].…”
Section: Methodsmentioning
confidence: 99%
“…GDLC was chosen in this study because it has been widely used by previous researchers and has proven to be an appropriate game development method if implemented in game design. This method has simple steps and is by the conditions in this study as shown in Figure 1 [18][19] [20].…”
Section: Methodsmentioning
confidence: 99%
“…To name some authors such as (Laamarti et al, 2014;Vlachopoulos & Makri 2017;Zhonggen 2019;Roedavan et al, 2021) who present reviews on serious games in areas such as education, well-being, advertising, cultural heritage, interpersonal communication, and health care. (Pacheco 2022) introduces a serious game to teach logistical concepts.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In addition, the emergence of game-based approaches in non-game contexts has led to the concept of serious games, which involves the use of digital games for educational purposes using full-fledged games (Gurbuz & Celik, 2022;Krath et al, 2021). The distinction lies in the fact that serious learning applies to only digital games, whereas gamification and game-based learning involves the methodologies employed (Roedavan et al, 2021). Franzwa et al (2014) summarized three game mechanisms for designing gamification platforms that are fun, reduce frustration, and maintain a balance between enjoyment and learning: feedback in the form of rewards, instructional information that is aligned with the game's environment and story, and the delivery of instructions in short cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the emergence of game-based approaches in non-game contexts has led to the concept of serious games, which involves the use of digital games for educational purposes using full-fledged games (Gurbuz & Celik, 2022; Krath et al, 2021). The distinction lies in the fact that serious learning applies to only digital games, whereas gamification and game-based learning involves the methodologies employed (Roedavan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%